Social capital and self-rated health: experiences from Makete district, Tanzania - Frumence, Gasto; Nyamhanga, Tumaini M. (Tanzania Journal of Health Research, 2017)
Background: It is almost two decades since various research works started documenting the debate surrounding the role of social capital on individual health outcomes in different contexts. However, in Tanzania there is a dearth of empirical evidence showing how social capital influences health outcomes. The objective of this study was to investigate the links between individual social capital and self-rated health by selected socio-demographic factors. Methods: We conducted a population-based cross-sectional study in Makete district in the south-western Tanzania. A semi-structured questionnaire was used to collect data using face to face interviews with the study participants. We collected information on individual structural social capita, which include memberships in organizations, giving social support, receiving social support and participation in voluntary activities. We also collected information on individual cognitive social capital including visiting neighbour, trusting neighbour, interaction with neighbour and ability to influence in decisions. Results: A total of 862 individuals from four villages participated in the study with the mean age of 31.3 years. Factor analysis (using principal components analysis) with varimax determined four domains of structural social capital: participation in collective activities, giving social support, membership in formal and informal organizations and receiving social support (factor loadings: 0.65 to 0.55). Four domains of cognitive social capital were also identified: visiting a sick neighbour, trusting a neighbour, and interacting with neighbour and ability to influence decisions (Factors loadings: 0.78 to 0.52). The multivariable logistic regression analysis shows that individuals with access to medium and high levels of structural social capital were almost 2 and 3 times more likely to report good health than individuals with low social capital [OR 2.3 (CI: 1.6-3.4)] and [OR 3.4 (CI: 2.3-5.1)], respectively. Conclusion: Our study findings support the argument that high level of structural social capital has positive health outcomes in rural Tanzania’ setting. Therefore, village leaders in particular and community members in general should promote social capital in their communities as one of the health interventions towards improving individual health.